2012
DOI: 10.1155/2012/463985
|View full text |Cite
|
Sign up to set email alerts
|

7-Day Nonbismuth-Containing Concomitant Therapy Achieves a High Eradication Rate forHelicobacter pyloriin Taiwan

Abstract: Background. Ten-day concomitant therapy achieves a high eradication rate in Taiwan. Whether shortening the duration of concomitant therapy can still keep a high eradication rate remains unclear. Aim. To assess the eradication rate of 7-day pantoprazole-containing concomitant therapy in Taiwan and to investigate factors influencing the eradication outcome. Methods. From March 2008 to March 2012, 319 H. pylori-infected patients receiving a 7-day pantoprazole-containing concomitant regimen (pantoprazole 40 mg, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The promising data presented here are consistent with a head-to-head noninferiority trial of 10-day sequential and 10-day concomitant therapy by our group showing comparable eradication rates (93.0% vs 93.1%) for H. pylori eradication [24]. Concomitant therapy is a four-drug regimen containing a PPI [30]. This therapy is superior to standard triple therapy for H. pylori eradication [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The promising data presented here are consistent with a head-to-head noninferiority trial of 10-day sequential and 10-day concomitant therapy by our group showing comparable eradication rates (93.0% vs 93.1%) for H. pylori eradication [24]. Concomitant therapy is a four-drug regimen containing a PPI [30]. This therapy is superior to standard triple therapy for H. pylori eradication [31].…”
Section: Discussionsupporting
confidence: 89%
“…), and metronidazole (500 mg, b.i.d.) which are all given for the entire duration of therapy . This therapy is superior to standard triple therapy for H. pylori eradication .…”
Section: Discussionmentioning
confidence: 99%
“…11 More recently, multiple trials of concomitant NBQT have confirmed an ITT eradication rate of 75-96.4% (per-protocol rates consistently superior to 80%) with a possible advantage for longer treatment duration (Table 3). 15,16,[21][22][23][24][25][26][27][28][29][30][31][32] The results of this randomized trial appear to confirm our earlier observation 13 that reduced-dose regimens (down to 50% posology) performs similarly to standard-dose regimens with the added benefit of reduced cost and adverse events. To date, three randomized controlled trials, involving a total of 475 patients, have examined the value of 50% reduction in the dose of all administered antibiotics for H. pylori (two STT and the current concomitant NBQT) and have all confirmed similar eradication rates to the standard-dose comparator (Table 4), with a reduction in adverse events and cost.…”
Section: Discussionsupporting
confidence: 80%
“…In Taiwan, Kao SS et al. reported that 7 days of a concomitant regimen (pantoprazole 40 mg, amoxicillin 1 g, clarithromycin 500 mg, and metronidazole 500 mg twice daily for 7 days) achieved a high H. pylori eradication rate (93.7% by ITT and 96.4% by PP). Wu et al.…”
Section: Eradication Of H Pylori Infectionmentioning
confidence: 99%
“…In Taiwan, Kao SS et al reported that 7 days of a concomitant regimen (pantoprazole 40 mg, amoxicillin 1 g, clarithromycin 500 mg, and metronidazole 500 mg twice daily for 7 days) achieved a high H. pylori eradication rate (93.7% by ITT and 96.4% by PP) [66]. Wu et al [67] obtained similar results in another study, the ITT eradication rate reached 93.0% after concomitant therapy, and the authors concluded that concomitant therapy may be more suitable for patients with dual resistance to antibiotics.…”
Section: Concomitant Therapymentioning
confidence: 99%